Studi Pendahuluan Potensi Carbon Capture Storage (CCS) Melalui Identifikasi Sumber Emisi CO2 beserta tinjauan geologi di Daerah Probolinggo, Jember, dan Bondowoso, Jawa Timur - Sari, Riska Laksmita; Haeruddin, Haeruddin (Universitas Tanjungpura, 2024)
Carbon dioxide (CO2) is a gas compound that causes the greenhouse effect. The majority of carbon dioxide gas production is dominated by large industrial industries such as Coal Steam Power Plants (PLTU), the cement industry and fossil fuel motorized vehicles (Hydrocarbons). Several technologies have been implemented and developed, in an effort to reduce the negative impact of CO2 accumulation on the earth's surface. One of them which is currently a topical topic is Carbon Capture Storage (CCS). CCS is a storage system used to receive and store carbon releases from industry and power plants into geological formations safely and permanently with a certain capacity for a long period of time. CCS is seen as a very efficient method because it can balance achieving net zero emissions while maintaining energy security. In this research, a preliminary study was carried out in the initial step of identifying potential sources of CO2 emissions along with a review of geology as a potential CO2 storage. In the Probolinggo, Jember and Bondowoso areas. From the identification results, it was concluded that the Paiton PLTU area in Probolinggo has the largest potential for CO2 production, around 1.98 million tons/year. The grological scope of the Paiton PLTU area meets one of the CO2 Storage criteria because the formation is included in the East Kendeng sedimentary zone. However, further studies need to be carried out to validate the potential for CO2 storage in further geological, petrophysical and fault analysis